Assessing dependency of part properties on the printing location in laser-powder bed fusion metal additive manufacturing. (March 2022) - Mussatto, Andre; Groarke, Robert; Vijayaraghavan, Rajani K.; Hughes, Cian; Obeidi, Muhannad Ahmed; Doğu, Merve Nur; Yalçin, Mustafa Alp; McNally, Patrick J.; Delaure, Yan; Brabazon, Dermot
Abstract: Despite the accelerated growth of laser-powder bed fusion in recent years, there are still major obstacles to be overcome before the technology enjoys truly widespread adoption. These include inconsistent part quality and repeatability issues linked to variability in the properties of printed parts. Commonly, the print location across the build platform is overlooked and assumed to have little or no effect on the overall part properties. There is a lack of previous systematic studies and a lack of knowledge of the influences of the location parameter on the final part properties. Therefore, to address the existing problem, the current study completely isolated the location parameter to accurately assess any effect of this variable on the microstructure and mechanical properties of laser-powder bed fusion manufactured parts. The results revealed the importance of the build location and showed that there is correlation between the location parameter and part properties as qualitative and quantitative properties of printed parts varied between the selected extremity locations. The findings highlight the importance of considering the location of the part being printed on the build platform and how the location may need to be fixed for multiple builds in order to achieve acceptable repeatability.